Matemática, perguntado por fernandacarlovichi17, 1 ano atrás

1)
Calcule:
a) (+6)-(-3) =
h) (+7) - (-6) =
b) (+4) - (-2) =
i) (-3) - (-4) =
c) (-2) - (+8) =
j) (+4) + (-2) + (-5) =
+
d) (+1)-(-4) =
k) (+10) + (+9) +(-2) =
e) (+3) - (+8) =
1) (+7) + (-8) + (-1) =
f) (+10) - (+10) =
m) (-6) + (-2) + (+1) =
n) (-9) + ( +7) + (-2) =
g) (-9) - (+5) =​

Soluções para a tarefa

Respondido por aylencoca9
2

Resposta:

a- 9

h- 13

b- 6

i - 1

c - -10

i - -2

Explicação passo-a-passo:

d- 5

k- 17

e- -5

1-14

f- 0

m- -7

n - -4

g- -14

Perguntas interessantes